In silico genome-scale metabolic modeling and in vitro static time-kill studies of exogenous metabolites alone and with polymyxin B against Klebsiella pneumoniae - Chung, Wan Yean; Abdul Rahim, Nusaibah; Mahamad Maifiah, Mohd Hafidz; Hawala Shivashekaregowda, Naveen Kumar; Zhu, Yan; Wong, Eng Hwa (Frontiers in Pharmacology, 2022)
Multidrug-resistant (MDR) Klebsiella pneumoniae is a top-prioritized Gram-negative pathogen with a high incidence in hospital acquired infections. Polymyxins have resurged as a last-line therapy to combat Gram-negative 'superbugs' including MDR K. pneumoniae. However, emergence of polymyxin resistance has increasingly been reported over the past decades when used as monotherapy and thus combination therapy with non-antibiotics (e.g., metabolites) becomes a promising approach owing to lower risk of resistance development. Genome-scale metabolic models were constructed to delineate the altered metabolism of New Delhi metallo-β-lactamase or extended spectrum β-lactamase producing K. pneumoniae strains upon addition of exogenous metabolites in media. The metabolites caused significantly metabolic perturbations were then selected to examine their adjuvant effects using in-vitro static time-kill studies. Metabolic network simulation shows that feeding of 3-phosphoglycerate and ribose 5-phosphate would lead to enhanced central carbon metabolism, ATP demand and energy consumption, which is converged with metabolic disruptions by polymyxin treatment. Further static time-kill studies demonstrated enhance antimicrobial killing of 10 mM 3-phosphoglycerate (1.26 and 1.82 log10 CFU/mL) and 10 mM ribose 5-phosphate (0.53 and 0.91 log10 CFU/mL) combination with 2 mg/L polymyxin B against K. pneumoniae strains. Overall, exogenous metabolite feeding could possibly improve polymyxin B activity via metabolic modulation and hence offers an attractive approach to enhance polymyxin B efficacy. With the application of GSMM in bridging the metabolic analysis and time-kill assay, biological insights of metabolite feeding can be inferred from comparative analyses of both results. Taken together, a systematic framework has been developed to facilitate the clinical translation of antibiotic-resistant infections management.